Avaliação dos patótipos de Escherichia coli circulantes no rebanho bovino e identificação das cepas de STEC isoladas no estado de São Paulo - Spina, Thiago Luiz Belém [UNESP] (2015)
Beef can be an important vehicle for various pathogens to humans, especially Shiga toxin-producing Escherichia coli (STEC), associated to human and animal diarrhea. In this study, the prevalence of different pathotypes of diarrheagenic E. coli, and virulence profiles of STEC were investigated among feces of cattle slaughtered in São Paulo state, southeast of Brazil. From a total of 431 animals, STEC was identified from 116 (26,9%) samples, being 111 (25,8%) STEC eae- and 5 (1,1%) STEC eae+. EPEC pathotype was detected among 20 (4,6%) of animals. The other pathotypes of diarrheagenic E. coli were not identified. Of the 95 STEC isolates assessed for virulence profile, all harbored stx2, while 28 (29,5%) contained stx1. Iha and saa, genes encoding adhesins, were found at 93,7% (89/95) and 66,3% (63/95), respectively. EspP, gene which encoding a protease related with intestinal colonization, was detected in 61,1% (58/95) and ehxA hemolysin was present in 54,7% (52/95). SubAB, nleE and nleB genes were also detected in lower rates. STEC is widespread in cattle herds of São Paulo, containing commonly isolated genes from human pathogens, which reinforces the importance of inspection and surveillance in the slaughterhouses